Roots of futility - Polansky, Norman A.; Borgman, Robert D.;De Saix, Christine (San Francisco, California : Jossey-Bass Inc., Publishers, 1972)
This book began not with a design but with a dream.
1. Poor as Job's turkey -- 2. When is a child neglected? -- 3. Desolation -- 4. Futility in a cultural context -- 5. Design of a diagnostic study -- 6. Psychic maturity and maternal competence -- 7. Transmission of futility -- 8. Impact of a child -- 9. Infantilization -- 10. Verbal accessibility in diagnosis -- 11. Exercise in futility -- 12. Breaking the chain.
Includes bibliographical references and index.
Keywords: BEHAVIORAL